READABILITY OF ENGLISH WRITTEN MATERIALS - Nur Rachma Isnaeni (Elite : English and Literature Journal, 2013)
AbstractThe best way to ensure readability of the content is by look out for principles in clear writing. In theory this means avoiding many long syllable words, unusual words, or long and awkward sentences.This study analyzed how readable is English written materials used for high school students and what factors do the readability of written language affect. To answer these, a descriptive quantitative research has been conducted and the English written materials taken as a subject. It is found that The Fog Index provides numerous benefits for many people include educators, librarians, publishers, and even students. Most importantly, it allows us to shape and edit our writing for a particular audience. AbstrakCara terbaik untuk memastikan keterbacaan isi buku adalah dengan melihat prinsip-prinsip dalam menulis.Dalam teori, ini berarti menghindari banyak kata yang panjang suku kata, kata-kata yang tidak biasa, atau kalimat yang panjang dan canggung. Studi ini menganalisis bagaimana keterbacaan materi tertulis bahasa Inggris yang digunakan oleh siswa SMA dan faktor-faktor apayang mempengaruhi keterbacaan materi. Untuk menjawab ini, penelitian deskriptif kuantitatif telah dilakukan dan materi tertulis bahasa Inggris diambil sebagai subjek.Hasil menunjukkan bahwa Fog Index memberikan pengaruh positif bagi banyak orang termasuk pendidik, pustakawan, penerbit, dan bahkan siswa dalam memahami materi tertulis bahasa Inggris. Yang paling penting, memungkinkan kita untuk membentuk dan mengedit tulisan kita untuk pembaca tertentu.